Prediction of yard crane operation sequence and vehicle departure times at a yard block in container terminals - Pang, Pangianto (2012)
There are three main types of container handling equipment in container terminal; Quay Cranes (QC), vehicles and Yard Cranes (YC). Their operations are highly inter-dependent. An optimal coordination of between these equipments can make the terminal operating like an whole machine as these operation can smoothly work with each other. The overall objective of the terminal process is to maximizing the berth utilization by minimizing the total tardiness of jobs.